A STUDY ON THE SPEAKING ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 10 PEKANBARU - Famela Suryani; Mahdum,Ph.D '; Dr. Effendy Gultom,M.A (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was a study on the speaking ability of the second year students of SMAN 10 Pekanbaru.The aim of this research was to know about the second year students speaking ability at SMAN 10 Pekanbaru. The population of this research was the second year students of SMAN 10 Pekanbaru that divided into 9 classes, with total 297 students. The sample of this research was class X1 IPA 2, XI IPA 3, XI IPA 4, and XI IPS 2, with total 117 students.The instrument of this research was interview. In conducting this research, there were ten questions in interview which used to know the students’ speaking ability based on five aspects: pronunciation, grammar, vocabulary, fluency, and comprehension. To get the quantitative data in this research, the three raters were involved to give the scores of students speaking ability. From the result of the oral test in five aspects of speaking ability, the writer concluded that the average score of students’ ability in speaking from the first rater was 57.74, it was categorized as mediocre level. From the second rater was 58,15, it was categorized as mediocre level. From third rater it was 58,54 it was categorized as mediocre level. From the three raters in five aspects of speaking ability, the average of speaking ability of students at the second year of SMA Negeri 10 Pekanbaru were 58.14, it was categorized into mediocre level. The research finding also shows that students got the highest mean score in terms comprehension and got the lowest mean score in terms of pronunciation.Keywords : descriptive research, students’ speaking ability